Assessment of development results : evaluation of UNDP contribution : Armenia - United Nations Development Programme; Independent Evaluation Office (New York : United Nations Development Programme, Independent Evaluation Office, 2014)
"This is the first ADR assessment of UNDP's contribution to Armenia, and it covers the period 2005-2013..The collapse of the Soviet Union led to profound economic and societal changes in Armenia. Since the country's independence in 1991, UNDP's programme in Armenia has been closely aligned with national plans and priorities and also with UNDP's mandate to support human development and address poverty and inequalities. The evaluation found that since 2005, UNDP has enjoyed a high profile in Armenia...During the assessment period, UNDP also made significant contributions to help Armenia respond to the needs of vulnerable groups through its work on human rights protection, gender equality and HIV/AIDS...To increase UNDP's strategic contributions, the evaluation suggests that UNDP's next programme should focus on fewer, more strategically targeted outcomes." --From the Foreword by Indran Naidoo.
Keywords: UNDP (Armenia) -- Evaluation; Economic development projects -- Evaluation -- Armenia; Economic assistance -- Evaluation -- Armenia